(E)-1-(4-Bromophenyl)-3-(3,4,5-trimethoxyphenyl)prop-2-en-1-one - Suwunwong, Thitipone (International Union of Crystallography, 2008)

(untitled)
In the title compound, C(18)H(17)BrO(4), the dihedral angle between the 4-bromophenyl and 3,4,5-trimethoxyphenyl rings is 44.18 (6)°. In the crystal structure, the molecules are linked by C—H⋯O and C—H⋯π interactions.